Réponses

Meilleure réponse !
2014-03-20T23:11:36+01:00
Bonsoir, 

A = (x + 5)(2x + 1) + 6 (2x + 1)
   = (2x + 1) [(x + 5) + 6]
   = (2x + 1) (x + 5 + 6)
   = (2x + 1) (x + 11)

B = 8x (5x - 1) - 8x (12 - x)
   = 8x [(5x - 1) - (12 - x)]
   = 8x (5x - 1 - 12 + x)
   = 8x (6x - 13)

C = 5 (2x + 3) - (3x - 8)(2x + 3)
   = (2x + 3) [5 - (3x - 8)]
   = (2x + 3) (5 - 3x + 8)
   = (2x + 3) (13 - 3x) 

D = (1 - 2x)(9x - 1) - (9x - 1)(7 + 3x)
   = (9x - 1) [(1 - 2x) - (7 + 3x)]
   = (9x - 1) (1 - 2x - 7 - 3x)
   = (9x - 1) (-5x - 6)

E = (a - 5)(7 + b) - (7 + b)
   = (a - 5)(7 + b) - 1 * (7 + b)
   = (7 + b) [(a - 5) - 1]
   = (7 + b) (a - 5 - 1)
   = (7 + b) (a - 6)

F = 3x + 1 + (3x - 1)(3x + 1)
   = 1 * (3x + 1) + (3x - 1)(3x + 1)
   = (3x + 1) [1 + (3x - 1)]
   = (3x + 1)(1 + 3x - 1)
   = (3x + 1) * (3x)
   = 3x(3x + 1)